“There was Rowdyism there, Boy”: Exploring How Old-Time Wakes Are Remembered in the Maritimes - MacDonald, Shamus (Ethnologies, 2022)
Drawing on sources in English, French, and Gaelic, this article explores accounts of tricks, pranks, and merriment at traditional house wakes in Maritime Canada. Using evidence from contemporary fieldwork and historic descriptions of these gatherings, it demonstrates how narratives describing these activities articulate conflicting attitudes about their propriety and suggests how tradition bearers may reinterpret accounts of what occurred at wakes in order to construct an image of the past that is more acceptable to the present.